“Endothelium-Out” and “Endothelium-In” Descemet Membrane Endothelial Keratoplasty (DMEK) Graft Insertion Techniques: A Systematic Review With Meta-Analysis - Ong, Hon Shing; Htoon, Hla M.; Ang, Marcus; Mehta, Jodhbir S. (Frontiers in Medicine, 2022)
Background We evaluated the visual outcomes and complications of ‘endothelium-out’ and ‘endothelium-in’ Descemet membrane endothelial keratoplasty (DMEK) graft insertion techniques. Methods Electronic searches were conducted in CENTRAL, Cochrane databases, PubMed, EMBASE, ClinicalTrials.gov. Study designs included clinical trials, comparative observational studies, and large case series (≥25 eyes). PRISMA guidelines were used for abstracting data and synthesis. Random-effects models were employed for meta-analyses. Results 21,323 eyes (95 studies) were included. Eighty-six studies reported on ‘endothelium-out’ techniques; eight studies reported on ‘endothelium-in’ techniques. One study compared ‘endothelium-out’ to ‘endothelium-in’ techniques. Eighteen ‘endothelium-out’ studies reported that 42.5% to 85% of eyes achieved best-corrected visual acuity (BCVA) ≥20/25 at 6 months; pooled proportion of eyes achieving BCVA ≥20/25 at 6 months was 58.7% (95% CI 49.4% to 67.7%,15 studies). Three ‘endothelium-in’ studies reported that 44.7 to 87.5% of eyes achieved BCVA of ≥20/25 at 6 months; pooled proportion of eyes achieving BCVA ≥20/25 at 6 months was 62.4% (95% CI 33.9% to 86.9%). Pooled mean endothelial cell loss was lower in the ‘endothelium-in’ studies (28.11.3%, 7 studies) compared to ‘endothelium-out’ studies (36.36.9%,10 studies) at 6 months (p=0.018). Graft re-bubbling rates were higher in the ‘endothelium-out’ studies (26.2%, 95% CI 21.9% to 30.9%,74 studies) compared to ‘endothelium-in’ studies (16.5%, 95% CI 8.5% to 26.4%,6 studies), although statistical significance was not reached (p=0.440). Primary graft failure rates were comparable between the two groups (p=0.552). Quality of evidence was considered low and significant heterogeneity existed in the studies. Conclusions Report rates of endothelial cell loss were lower in ‘endothelium-in’ DMEK studies at 6 months compared to ‘endothelium-out’ studies. Outcomes of ‘endothelium-in’ techniques were otherwise comparable to those reported in ‘endothelium-out’ studies. Given the technical challenges encountered in ‘endothelium-out’ procedures, surgeons may consider ‘endothelium-in’ techniques designed for easier intra-operative DMEK graft unfolding. ‘Endothelium-in’ studies evaluating outcomes at longer timepoints are required before conclusive comparisons between the two techniques can be drawn.